Reducing missed medication doses in intensive care units: A pharmacist-led intervention - Mukhtar Jawad Alomar; Sohail Ahmad; Yahya Moustafa; Lafi Salim Alharbi (Wolters Kluwer Medknow Publications, 2020)
Objective: The objectives of this study were to investigate the frequency and reasons for missing doses and impact of a pharmacist-led intervention to reduce the missed doses in intensive care units. Methods: This study was completed in two phases. In the first phase, a retrospective quality assurance audit was conducted to quantify the problem of missed doses from the pharmacist/nurse communication slip record. The frequency and potential reasons for missing dose occurrences were identified and listed, and respective solutions were finalized by a joint health-care team. In the second phase of the study, post-intervention analysis was done for a period of 1 month to check the impact of intervention. The data were recorded from pharmacy/nursing communication forms for medication, dosage form, route of administration (ROA), frequency of missed doses, and underlying reasons for missing doses. Findings: There was a substantial reduction in the number of incidences of missed doses in post-intervention phase. The number of events decreased from 190 (pre-intervention; 2 months) to 11 (post-intervention; 1 month), 389 to 87, and 133 to 12 for automatic stop order, unknown reason, and late mix medication, respectively. No missed dose event was recorded secondary to order overseen and inactive patient status in post-intervention phase. Moreover, identified reasons, ROA, frequency, and the system status were the significant predictors of missing doses. Conclusion: The findings of this study emphasized the need to introduce better documentation procedures and continuous surveillance system to decrease the number of missing doses and further improve already established drug distribution service.